Performance of animal fat-based biodiesel on micro-gas turbine - Alrashidi, Naser A Z S (2019)
Biodiesel is a fuel that produced from several bio-materials such as waste cooking oil, vegetarian oil, animal fats (tallow’s) etc. The present study is about using a biodiesel that produced from animal tallow’s to operate a small jet engine. The jet engine has been specially designed to test and investigate the effect of biodiesel from animal tallow on the thermal efficiency of the jet engine. Measure the power of engine in all of the situations and the amount of emissions extracted from turbine using fossil diesel, kerosene, B20, B50, B75 and B100 respectively. These biodiesel fuel properties were analysis based on the international standard. Also, the amount of emissions and the operating performance (temperature and pressure) of micro gas turbine were conducted. A control unit has been designed to ensure a stable operation. The jet engine was tested under 3 levels of load (low, medium, high). A primary and secondary fuel cycle is used to change from using fossil fuel to biodiesel. The results of the biodiesel fuel were found that they are within the acceptable range of the international standard. Also, the results showed that the amount of oxygen emission changes between 16.4% and 16.8%, and carbon monoxide (CO) emissions in the biodiesel blends (B20, B50, B75 and B100) change between 0.04% and 0.18%. The emission of carbon dioxide in B100 and diesel fuel is the same and the kerosene fuel is the lowest in all stages of operation in the production of carbon dioxide (CO2) emission changes from 2.7% to 3.0%, reduction in nitrogen oxides (NOx) compared to fossil fuels. Nitrogen dioxide (NO2) is low in operation high load of B50, B20, B75 but in B100 it is too high emission changes between 4 ppm to 15 ppm. The performance of micro gas turbine based on the biodiesel fuel was found better than the fossil fuel in general. The results found in this study indicated that the biodiesel blends used is applicable and demonstrated great potential to be used as an alternative fuel to operate small engine with B20 was economically and less polluting the environment.